2020
DOI: 10.1002/mds.28376
|View full text |Cite
|
Sign up to set email alerts
|

Resting‐State Functional Connectivity Predicts STN DBS Clinical Response

Abstract: Background Deep brain stimulation of the subthalamic nucleus is a widely used adjunctive therapy for motor symptoms of Parkinson's disease, but with variable motor response. Predicting motor response remains difficult, and novel approaches may improve surgical outcomes as well as the understanding of pathophysiological mechanisms. The objective of this study was to determine whether preoperative resting‐state functional connectivity MRI predicts motor response from deep brain stimulation of the subthalamic nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 42 publications
(97 reference statements)
2
23
0
Order By: Relevance
“…As such, therapeutic response to stimulation may be a direct result of a stimulation-induced change from aberrant to healthy network-level functional connectivity. This change may in turn be determined by the underlying network-level functional connectivity, as recent work has indicated that underlying functional connectivity shapes the therapeutic response to stimulation [23][24][25], and here we have also shown that it shapes stimulationinduced network-level FCC. Further work which holistically studies the underlying network, neural stimulation, FCC, and neural disorders is needed.…”
Section: Network-level Analysis Of Neural Stimulationsupporting
confidence: 66%
See 1 more Smart Citation
“…As such, therapeutic response to stimulation may be a direct result of a stimulation-induced change from aberrant to healthy network-level functional connectivity. This change may in turn be determined by the underlying network-level functional connectivity, as recent work has indicated that underlying functional connectivity shapes the therapeutic response to stimulation [23][24][25], and here we have also shown that it shapes stimulationinduced network-level FCC. Further work which holistically studies the underlying network, neural stimulation, FCC, and neural disorders is needed.…”
Section: Network-level Analysis Of Neural Stimulationsupporting
confidence: 66%
“…Recent research indicates that network-level functional connectivity is not only a↵ected by stimulation but also is involved in shaping the response to stimulation. For example, underlying functional connectivity has been shown to shape stimulation-induced neural activity propagation [18][19][20][21][22] as well as influence the therapeutic outcome of neural stimulation interventions for Parkinson's disease [23,24] and depression [25]. Early results have also indicated that network-level FCC induced by stimulation are correlated to baseline functional connectivity [11,17,26].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, imaging studies demonstrated the predictive value of structural and functional connectivity for motor outcome of STN-DBS in PD patients based on diffusion tensor imaging (DTI) ( Horn et al, 2017 ) and resting-state functional MRI (rs-fMRI) ( Younce et al, 2020 ). Smaller ventricular volumes measured on T1 weighted images were associated with more favorable motor outcome in one report ( Younce et al, 2019 ) but not in others ( Price et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study conducted RA-ML analysis of specific motor outcome which is not available in most previous studies ( Price et al, 2011 ; Lönnfors-Weitzel et al, 2016 ; Horn et al, 2017 ; Younce et al, 2019 , 2020 ). Cardinal motor symptoms in PD patients include rigidity, bradykinesia, and tremor.…”
Section: Discussionmentioning
confidence: 99%
“…32 Preoperative FC between STN and the ipsilateral globus pallidus internus (GPi) has also been shown to be positively correlated with clinical improvement after STN-DBS in Parkinson's disease. 33 In contrast, there is far less known about preoperative FC and DBS outcomes in patients with idiopathic generalized dystonia, however a recent study positively correlated preoperative FC between lead site (GPi) and primary sensorimotor cortex, motor thalamus, and cerebellum. 34 It should be noted that several of these connectivity studies also utilize structural connectivity (T2 diffusion imaging) although FC often independently predicts DBS outcomes.…”
Section: Diseasementioning
confidence: 99%